Overproduction and Purification of Soluble Recombinant Human Granulocyte Colony Stimulating Factor in Escherichia coli Using Thioredoxin as Fusion - Agustiyanti, Dian Fitria; Retnoningrum, Debbie Sofie; Rachmawati, Heni; Fuad, Asrul Muhamad (BRIN, 2017)
Recombinant human Granulocyte Colony Stimulating Factor (G-CSF) has been produced in a soluble form in Escherichia coli BL21 (DE3) as a fusion protein. The open reading frame of G-CSF was synthetically constructed in previous work and was codon optimized for best expression in E. coli. In this research, the gene was fused to thioredoxin (Trx) at the N-terminal in pET32 vector. The purpose of this research was to optimize the overproduction and purification processes to obtain high yield recombinant protein in soluble form, and to characterize the Trx-G-CSF fusion protein. Overproduction was performed using IPTG induction method for 3 and 6 hours. The protein was purified by Ni-NTA affinity chromatography and separated using gradient concentration of imidazole. The purified protein was then characterized by SDS-PAGE and Western Blot analysis. Further, enterokinase was used to separate G-CSF from the fusion protein. The purified form of G-CSF was subsequently characterized using Western Blot and mass spectrometry using MALDI-TOF. The results showed that the fusion protein was successfully produced in soluble part as much as 48.25% were obtained after 3 hours of induction. The yield of fusion protein was 67.37% from total protein (229.65 mg protein/L culture). The Western Blot analysis showed the G-CSF band at around 18.6 kDa. Mass spectrometry with MALDI-TOF/ TOF revealed that 25.86% of amino acid residue was recognized as part of human G-CSF sequence.